Game Theoretic Spatial Evacuation Simulation Models To Predict Crowd Disaster - Ibrahim, Azhar Mohd (2018)
Crowd dynamics play an important role in evacuation management systems relevant to organizing safer large scale gatherings. Planning crowd control tasks via evacuation simulation of the movement and behaviours of crowd during egress could mitigate the possibility of crowd disasters that may happen. Previous studies on evacuation models do not describe the uncertainly faced by the agents in in making decisions when conflicts among agent occur. Beside, most of the studies have proposed evacuation models over a discrete space and have assumed that the agent's cost function that describe how the agents view the importance of evacuation scenario to be constant.